Optimization processability of ss316l used natural hydroxyapatite from waste tilapia fish bones in metal injection molding - Mustafa, Najwa (2019)
Application of waste Tilapia Fish bones is introduced as a Natural Hydroxyapatite (NHAP) powder in metal injection moulding. Feedstock were prepared based on water atomized Stainless steel 316L (SS316L) and combination of NHAP powder bind with Low density Polyethylene (LDPE) and Palm stearin (PS). The results of rheological analysis show feedstocks with 63 and 64 wt.% of powder loading for both 90 wt.% SS316L and 10 wt.% NHAP and 85 wt.% SS316L and 15 wt.% NHAP composites shows a pseudoplastic behaviour. The screening of injection moulding and thermal debinding were conducted by using ANOVA. The significant parameters towards highest density and strength for injection moulding are injection temperature (A), mould temperature (B), injection pressure (C), and injection speed (D). Moreover, the significant parameters for thermal debinding were heating rate (A), temperature (B), dwell time (C), and cooling rate (D). The entire parameters have achieved the confident level above 90% using F-test and any interactions of A×B, A×C, and B×C were omitted since the results were insignificant. Taguchi method and Grey relational analysis was successfully employed for optimising the injection and debinding parameters. The optimisation of injection moulding process revealed the optimum condition for multiple response (density and strength) was injection temperature at 170 °C, mold temperature at 50 °C, 65 % of injection pressure and 60 % of injection speed. The optimisation of solvent debinding discovered the highest density and palm stearin loss. The optimum parameter for multiple condition was 8 hours of immersion time at 40 °C by using hexane in dilution of 15:1 solvent to feed ratio. The extraction process indicates that hexane solution was better compared to heptane and isooctane with respected higher percentages of palm stearin loss. The optimal condition of thermal debinding process was heating rate at 4 °C/min, temperature at 550 °C, 60 minutes of dwelling time and 4°C/min cooling rate and produced good quality brown parts. The final sintered part also shows good mechanical properties and microstructure of SS316L/NHAP parts.